Faktor- Faktor yang Berpengaruh terhadap Produksi Selada Daun (Lactuca sativa var. crispa L) di Desa Baturiti, Kecamatan Baturiti, Kabupaten Tabanan - NI PUTU RAHAYU CHANDRA DEWI; RATNA KOMALA DEWI; DEWA GEDE RAKA SARJANA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2022)
Factors Affecting the Production of Lettuce (Lactuca sativa var.crispa L) in Baturiti Village, Baturiti District, Tabanan Regency. Lettuce (Lactuca sativa L) is a horticultural commodity that has high economic value. Lettuce can grow well if planted in an environment that suits its variety. Baturiti District is known as a lettuce-producer region. However, lettuce production has fluctuated due to inefficiency problems that are related with production inputs. This study aims to determine the factors that influence the lettuce production and the allocative efficiency to determine whether the use of production input factors is efficient or not in terms of price. The research was conducted in Baturiti Village by analyzing production factors such as arable land, seeds, manure, liquid pesticides, and labor using the Cobb-Douglass production function. Analysis was conducted by using data from the September to November 2019 planting season. The result shows that production factors such as arable land, manure and pesticides have a significant effect on lettuce production. The factors of seed production and labor do not have a significant effect on lettuce production. The use of manure and liquid pesticides is not efficient yet and must be added. The addition must meet the principles of “five right” for manure and “six right” for liquid pesticides in order to produce maximum profit.